Kinematic Analysis of Jasebaqeo Pparunbal Dollyuchagi Motion in TAEKWONDO - Kim, Seonghun; Heo, Boseob (International Journal of Martial Arts , 6(3), 2021)
Purpose: The purpose of this study is to compare and analyze pparun bal dollyuchagi(fast spin kick) motion of Taekwondo players, divided as outstanding ones and unskilled ones, to provide kinematic information on Taekwondo kicks and pparun bal dollyuchagi motion, and analyze differences in kicks between comparative groups. Method: The subjects of this study are Taekwondo players in their 20s who are attending the Taekwondo de-partment at K University, five outstanding ones who have won prizes at domestic competitions and five unskilled ones who have not won competitions. Prior to the experiment, the subjects were asked for consent and explained how to proceed with the experiment. Kinematic data were collected using eight digital cameras. Statistical pro-cessing in this study was conducted using SPSS 22.0 software, and statistical analysis values were calculated as mean(M) and standard deviation(SD). An independent sample t-test was conducted to analyze the differences between groups, and the statistical significance probability was set to p<0.05. Results: There was no significant difference in the total execution time during the comparative analysis be-tween the skilled and unskilled players of Jasebaqeo Pparunbal Dollyuchagi, and significant differences were found in the left and right variables of body center. Also, significant differences were found for each event in the hip, knee, and ankle joints of the lower extremities. Conclusion: According to the experiment, it is necessary to select an efficient hitting distance to improve the com- pleteness of the pparun bal dollyuchagi motion, and to hit the target, the width of the center of mass dis-place- ment on the left and right sides must be small and balanced without shaking. The knee joint and ankle joint should be quickly extended when striking a target, then vertically moved quickly to perform a perfect motion. This study is considered significant in that it provided fundamental data necessary for the efficient performance of kicks. KCI Citation Count: 1